Correction of microecological imbalance in children who have suffered from multisystem inflammatory syndrome associated with SARS‐CoV‐2 in the post‐rehabilitation period - T. I. Ryabichenko; O. O. Obukhova; M. I. Voevoda (Юг России: экология, развитие)
To conduct a study of the quality of life of children who have suffered from multisystem inflammatory syndrome (MIS‐C) associated with SARSCoV‐2 in the post‐rehabilitation period against the background of correction of microecological imbalance.The study involved 49 children aged 2 to 12 years who underwent MIS‐C associated with SARS‐CoV‐2 and received treatment in a hospital (DGKB No. 3 in Novosibirsk), and then underwent rehabilitation on an outpatient basis. The duration of rehabilitation was 7–8 weeks. All children were prescribed a course of additional rehabilitation for 30 days in order to correct microecological imbalance, which included: Biovestin, a dietary supplement in liquid form, containing bifidobacteria of the Bifidobacterium longum MC‐42 strain; the official drug, Kudesan, (active ingredient Coenzyme Q10); and the official drug, Succinic Acid. The assessment of physical, social, educational, emotional and psychological functioning, as well as quality of life as an integrating indicator before and after a comprehensive rehabilitation course using the parental form of the Reds OL Generic Core Scales questionnaire (Russian version) was carried out.After the rehabilitation course, children who underwent MIS‐C associated with SARS‐CoV‐2 showed signs of dysfunction of various organs and systems, which may be the result of an imbalance in the microbial ecosystem and requires mandatory correction. The introduction of a probiotic product and drugs affecting metabolic processes into the rehabilitation course led to a decrease in inflammatory reactions, as well as normalisation of metabolic processes and increased oxygenation, which improved the condition of the children and their quality of life.Federal Research Center for Fundamental and Translational Medicine (FRC FTM), Siberian Branch, Russian Academy of Sciences